Bujang Dayang Buku Alternatif Meningkatkan Minat Baca Siswa di SMP Negeri 1 Pangkalanbaru - Sri Mardiyah; Ratu Wardarita (Jurnal Didaktika Pendidikan Dasar, 2023)
This paper is motivated by the low reading interest of students in Pangkalanbaru 1 State Junior High School, so it is necessary to develop school literacy programs that are liked by students so that they can increase their reading interest. Among them is the Bujang Dayang Buku program. The Bujang Dayang Buku program is a program that involves all Pangkalanbaru 1 State Junior High School students to motivate them to visit the library more often and read as many books as possible each semester. Bujang Dayang Buku was chosen based on the number of visits to the library and the number of books read in one semester. The number of visiting students was monitored through the visiting book they filled, while the number of books read was based on how many books were borrowed and the contents could be understood by students by making a synopsis. From the visitor data obtained during the 2016/2017 to 2018/2019 academic year, there was an increase of around 546 visitors, while there were about 1,298 borrowers when compared to visitor data and borrower data from previous years. Thus, it can be concluded that the Bujang Dayang Buku program as an alternative can increase students' reading interest in SMP Negeri 1 Pangkalanbaru.